Clinical Epidemiology and Molecular Biology of Hepatitis C. Issue 10 (6th January 2016) - Silverman, Ann L.; Gordon, Stuart C.
Abstract : A major breakthrough in the diagnosis of non-A, non-B hepatitis occurred in 1989 with the isolation of the hepatitis C virus. This article reviews the molecular biology of hepatitis C, as well as the current tests approved and researched by the Food and Drug Administration that are used for its diagnosis. The known epidemiology of this virus based on the available diagnostic tests is described.